Building Evidence-Based Tobacco Treatment in the Eastern Mediterranean Region: Lessons Learned by the Syrian Center for Tobacco Studies. (14th March 2016) - Asfar, Taghrid; Ward, Kenneth D.; Al-Ali, Radwan; Maziak, Wasim
Abstract : The tobacco epidemic in Syria is characterised by high rates of cigarettes smoking in men and dramatic re-emergence of waterpipe smoking, especially among youths and women. The Syrian Center for Tobacco Studies (SCTS), an NIH-funded pioneer research and capacity building institution, has developed a research infrastructure and conducted three randomised clinical trials to develop and rigorously test culturally appropriate tobacco treatment programmes integrated into primary healthcare (PHC) centres. This review aimed to discuss challenges and lessons learned from the Syrian experience. Addressing these challenges may inform future cessation research activities in Syria and other developing countries. To develop a research infrastructure, the SCTS has established Syria's first IRB and trained physicians/medical students in both tobacco treatment and research methods. Main challenges to conduct the cessation trials were difficulties of coordination between the local and international collaborators; high Smoking Rates among PHC providers; lack of pharmacological agents used in tobacco treatment; and difficulties of conducting research in a politically volatile region. Strategies to overcome these challenges were ensuring an active and regular involvement of all investigators; and advocating for a national smoking cessation plan that involves training healthcare providers in smoking cessation treatment and make pharmacological agents used in smoking cessation available.